The impact of an educational curriculum according to the strategy of generative thinking on learning and cognitive achievement (Journal of the College of Basic Education, 2022)
This study deals with the treatment of alternative perceptions of mathematical concepts through learning with a strategy based on constructive learning, which is the generative learning strategy in teaching mathematical concepts.The research aims to identify:1- Preparing an educational curriculum based on the use of the generative learning strategy that suits the capabilities of the research sample.2 - Learn about the impact of the educational program on learning and knowledge acquisition in football